Re-desription of the tadpole of Pleurodema somuncuriensis (Cei, 1969) (Amphibia, Anura) - Barrasso, Diego Andrés (2013)
The monotypic genus Somuncuria was erected by Lynch (1978) on the basis of external morphology and osteology of the adults of Telmatobius somuncurensis Cei, 1969. In addition, Lynch remarked a general resemblance between Somuncuria and Pleurodema. The recent phylogenetic analysis by Faivovich et al. (2012) recovered Somuncuria nested into Pleurodema and closely related to Pleurodema bufoninum. According to Faivovich et al. (2012), these species have nearly identical sequences and additional study is required to establish populations identity. Pleurodema somuncurensis inhabits thermal springs at mid altitudes (500–800 ma.s.l.) in a restricted geographic range at Meseta de Somuncurá, Río Negro Province, Argentina (Cei, 1969).